Preparation of Atomically-Dispersed Gold on Lanthanum Oxide as Active and Stable Catalysts for the Low-Temperature Water-Gas Shift Reaction. - Lessard, Joseph. (2017)
Abstract: Clean hydrogen has been touted as the fuel of the future because, when combusted, it only produces water, an environmentally innocuous by-product. The technology that would use this H2 most efficiently is the fuel cell, which is capable of converting the chemical energy stored in H2 into electrical energy that can be used to power daily life. Such a device, though, requires very pure H2 as a fuel source without contaminating gases like CO that poison the platinum catalysts on the anode of low temperature fuel cells. The water-gas shift (WGS) reaction has been intensely studied as the most efficient way to remove CO from H2 feeds to fuel cell systems. In such a design, a WGS reactor would operate upstream of the fuel cell, at low temperature, to remove most or all of the CO from the feed. Additional systems could also be implemented to further reduce the CO content and remove other impurities (e.g. H2S). The current catalysts used in industrial WGS reactors are Cu/ZnO/Al2O3. However, these catalysts are pyrophoric, require lengthy activation procedures and show little thermal stability. Noble metal (Au, Pt, Pd, etc.) catalysts have recently received significant attention as potential alternatives to the industrial catalysts because they are non-pyrophoric and can be made more stable. In this thesis, Au highly dispersed on La2O3 was investigated as a novel catalyst for the WGS reaction. In particular, an anion adsorption technique was developed to deposit Au onto the La2O3 surface in a manner that would favor a strong interaction between the Au and the support. In this work, catalysts were prepared with four different techniques: colloidal deposition, co-precipitation, deposition-precipitation, and anion adsorption. These materials were characterized with electron microscopy (TEM), X-ray absorption spectroscopy (XAS), BET surface area measurements, X-ray photoelectron spectroscopy (XPS), and temperature programmed reduction (CO-TPR) studies. Additionally, Au/La2O3 was studied under WGS reaction conditions in both product-free and full reformate gas environments. Anion adsorption was found to produce the most active WGS catalyst compared to other gold preparation techniques on lanthana. Additionally, it was observed that high temperature treatments of 1% Au/La2O3 further activated these materials for the WGS reaction. In an effort to improve our understanding of the importance of reducible versus irreducible metal oxide supports in the WGS reaction, the surface oxygen of the active gold catalysts was examined and quantified. It was discovered that normalization of the reaction rates over Au/La2O3 by the amounts of active surface oxygen were comparable to the similarly normalized rates of Au supported on reducible metal oxides like CeO2 and FeOx.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Maria Flytzani-Stephanopoulos.; Committee: Howard Saltsburg, and George Kyriakou.; Keywords: Chemical engineering, and Chemistry.